Enhancing Cultural Awareness in Students at First Level at the UPTC in Sogamoso - Barrera Cárdenas, Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2013)
AbstractThis project examines cultural awareness of 16 students of the basic English level at the Universidad Pedagógica y Tecnológica de Colombia Sectional- Sogamoso. This intervention was used in order to betterapproach the students and improve the class environment. A KWL chart was used as strategy to encourage the participants. In order to answer the procedure of the first part of the KWL chart, an intervention wasused to clarify and motivate students to speak about their own cultural background. Findings suggest that culture could have an important place and its meaning attend a revision in the program at this institution.Also, the development of cultural awareness is visible in the EFL classroom. However this aspect must be discussed in order toincorporate it in the curriculum, the use of materials and methodology.Keywords: cultural awareness, English/ foreign language. Learner, Sociocultural, EFL classroom ResumenEste proyecto analiza la concienciación cultural en 16 estudiantes de inglés básico en la Universidad Pedagógica y Tecnológica de Colombia Seccional- Sogamoso. Esta intervención se hizo a fin de mejorar elambiente en la clase. Un cuadro de KWL se utilizó como estrategia para motivar a los estudiantes ha hablar de su propia cultura. Los resultados sugieren que la cultura puede tener un lugar importante en estainstitución. También, el desarrollo de la concienciación cultural en el salón de inglés como lengua extranjera es visible. Sin embargo, se debe promover la incorporación de aspectos culturales en los materialesy en la metodología de clase. . A fin de responder Palabras clave: concienciación cultural, inglés como lengua extranjera,  salón de inglés como lengua extranjera.